Az 1919-es rendkívüli szlovák népszámlálás - Spišák, Mónika (Közép-Európai Közlemények, 2011)
The 1919 extraordinary census of population in Slovakia conducted after the formation of the Czechoslovak Republic. At this time the borders of the new state were not clear. In 1919 was established the State Statistical Office but the cenzus was organized by the Minister Plenipotentiary for the Administration of Slovakia. It was decided to map the ethnic composition of Slovakia and it was also the first test of the new state administration. Ethnicity was the most significant piece of data collected. Finally 67% of all persons declared them selves “Czechoslovak”. Aside from ethnicity were researched other demographic variables, such as sex, age, marital status, household position, spoken languages, literacy and the confessional composition of the population. The final results of the census did not serve their main purpose and were not used at the peace conference in Paris. The results were published only in 1921 by which time the peace conference had alredy ended.